A model to integrate and assess water-energy-food nexus performance: South Africa case study - Nhamo, Luxon; Mabhaudhi, Tafadzwanashe; Mpandeli, S. (2019)
The main limiting factor impeding the operationalisation of the WEF nexus has been lack of metrics and tools to translate the concept into a fully-fledged operational framework to support policy and decision-making. This study developed a WEF nexus model by (i) defining WEF nexus sustainability indicators, and (ii) calculating composite indices for those indicators to establish numerical relationships among WEF nexus resources using South Africa as a case study. The composite indices show WEF nexus performance as well as monitoring and evaluation of WEF resources management. The indicators were integrated through the Analytic Hierarchy Process (AHP) in a multicriteria decision-making (MCDM). The established quantitative relationships indicate resource utilisation, management and performance through a spider graph to illustrate WEF nexus performance, providing a general overview of the level of interactions, interrelationships and inter-connectedness of resources. The shape of the spider graph is determined by the level of the interdependencies and interactions among the WEF nexus sectors, whose management is viewed either as sustainable or unsustainable depending on the classification of the developed integrated index. The spider graph for South Africa showed an over-emphasis on food self-sufficiency and water productivity at the expense of other sectors. The deformed shape of the spider graph is a demonstration of the sectoral or “silo” approach in resource management. The calculated integrated WEF nexus index of 0.203 for South Africa classified the country under the low sustainability category. The developed model is a decision support tool that provides evidence for interventions in priority areas. The model demonstrates the capabilities of the WEF nexus to evaluate synergies and trade-offs in a systematic and integrated way to increases efficiency and productivity in resource management for sustainable development.